PENGARUH KEPUASAN KERJA DAN MOTIVASI TERHADAP KINERJA GURU SMA NEGERI 1 SUNGAI RAYA KABUPATEN KUBU RAYA - B11110144, NATALIA MERRY (Jurnal Manajemen Update, 2014)
This study, entitled "Effect of Job Satisfaction and Motivation Against Teacher performance SMA Negeri 1 Sungai Raya Kabupaten Kubu Raya". This study aims to determine how much Influence of job satisfaction and motivation on teacher performance SMA Negeri 1 Sungai Raya. The method used is a questionnaire survey and interviews as data collection techniques. As for the samples in this study is PNS SMA Negeri 1 Sungai Raya teachers with 45 people responden. The analysis techinique used this study is to test the validity and reliability test, the assumption of classical test, the product moment correlation and linier regression analysis which aims to determine the effect of each independent variabel on the dependent variable to make use of SPSS 18.0 program. While the hypothesis test usingthe test T to see koefsien partikal regression and F test to see regression coefficients simultaneously. Based on the results we concluded that the simultaneous significance test, it can be seen that job satisfaction and motivation variables jointly affect the performance of teachers. Indicated by the significant value of 0,001 F < 0,05 the result is supporter from the coefficient of determination (R-square) showed that 0,286 wre independent variables of job stasfaction and motivation are able explain 28,6 % of variation of change of the dependent variable is the performance of teachers. While the remaining 71,4 influenced by other factors not in the model inputs in this study. With partial significant test, only motivation variable significant positive effect on the teacherÂ  performance SMA Negeri 1 Sungai Raya. These results are consistent with a value of 0,001 T significance smaller than 0,05. Keywords: Job Satisfaction, Motivation, Performance.